The Interaction of Body Mass Index and Physical Activity on Menstrual Cycle Patterns in Female Students - Sri Musfiroh; Ahmad Nurjannah; Mazi Nurazmi (Ann Publisher, 2025)
Background. Menstrual cycle disruption is still a fairly high reproductive health problem in adolescents and young adults. Previous research showed that 38.6% of adolescents experienced irregular menstrual cycles, and 20.4% of them had experienced amenorrhea for ≥90 days. The regularity of the menstrual cycle is influenced by a variety of factors, including Body Mass Index (BMI) and physical activity. Aims. This study aims to analyze the interaction between Body Mass Index and physical activity on menstrual cycle patterns among regular female students at STIKes Muhammadiyah Cirebon in 2024. This study uses an analytical quantitative design with a cross-sectional approach. The sampling technique used was proportional stratified sampling with a total of 155 female students. Data were collected using a structured questionnaire, then analyzed using the Chi-Square test with a significance level of p ≤ 0.05. Result. The results showed a significant relationship between Body Mass Index and menstrual cycle patterns (p = 0.000; p < 0.05). Meanwhile, physical activity showed no significant association with menstrual cycle patterns (p = 0.08; p > 0.05). These findings show that BMI status plays a more dominant role than physical activity in influencing menstrual cycle patterns among female students. Conclusion. The conclusion of this study is that there is a partial interaction between Body Mass Index and menstrual cycle patterns, but no significant relationship was found between physical activity and menstrual cycle patterns. Implementation. The results of this study can serve as the basis for promotive and preventive efforts to maintain optimal BMI and support the reproductive health of female students.